Ensuring urgent environmental tasks and environmental safety - B. Tanirbergenov (Genius Journals, 2024)
The issue of environmental problems and emergency situations has risen to the level of state policy in the Republic of Uzbekistan. Many laws and decisions related to this field have been developed, and a state program has been adopted. In order to promote ecology and environment protection and its use at the policy level, the name of the ecology and environment protection committee was updated, and a program for the development of the ecological concept in the country was developed
Keywords: natural; anthropogenic; chemical